TINGKAT PENDAPATAN NELAYAN HAND LINE TUNA DI PELABUHAN PERIKANAN TELUK AWANG DESA MERTAK KECAMATAN PUJUT, KABUPATEN LOMBOK TENGAH - Cahayani, Mimi; Sayuti, Muhamad (Nusantara Hasana Journal, 2022)
Fisherman is one of the people's jobs around the coast. By becoming fishermen, people are able to have sufficient income and even more. There are various types of fishermen, one of which is hand line tuna fishermen. Therefore, the researcher wanted to examine "The Income Level of Hand-line Tuna Fishermen at Teluk Awang Fishery Port, Mertak Village, Pujut District, Central Lombok Regency". This type of research is quantitative with a descriptive approach. Data collection techniques using observation and interview methods, data collection tools using questionnaires, then the data is analyzed using income analysis. The results showed that the variable cost for one trip was Rp. 9,195,000, - and a fixed fee of Rp. 1.654.000,-. With a total cost of Rp. 10,849,000, - The total income earned by fishermen is Rp. 50,600,000, -. The profit sharing for hand line tuna fishermen consists of 5 parts of capital owners (Rp. 18,068,600,-), 3 parts of skipper (Rp 10,841,200,-) and 1 share of crew each (Rp. 3,613,700,-).